2010
DOI: 10.1007/s11442-010-0483-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and driving forces of land use change in China during the early 21st century

Abstract: 1947-), Professor, specialized in remote sensing of natural resources and environment, land use and cover change (LUCC) and ecological effect at macro-scale.Abstract: Land use and land cover change as the core of coupled human-environment systems has become a potential field of land change science (LCS) in the study of global environmental change. Based on remotely sensed data of land use change with a spatial resolution of 1 km × 1 km on national scale among every 5 years, this paper designed a new dynamic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
483
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 825 publications
(505 citation statements)
references
References 11 publications
12
483
3
7
Order By: Relevance
“…The total accuracy rate of land-cover classification exceeded 80%, as verified by a host of field surveys. This is the newest and most detailed land-cover dataset on the national scale in China (Liu et al, 2003(Liu et al, , 2010.…”
Section: Study Area and Land-cover Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The total accuracy rate of land-cover classification exceeded 80%, as verified by a host of field surveys. This is the newest and most detailed land-cover dataset on the national scale in China (Liu et al, 2003(Liu et al, , 2010.…”
Section: Study Area and Land-cover Datamentioning
confidence: 99%
“…This rapid development had a significant influence on land use and cover changes (LUCCs) and ESV changes (Liu et al, 2010) and led to an increasingly deteriorating environment in China . Recent literature has documented the negative effects (e.g., environmental pollution, soil erosion, natural disasters) on ecosystems that are associated with this rapid economic development (Diao et al, 2009;He et al, 2014;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The land use data were classified into 25 categories that were subsequently grouped into six classes: cropland, woodland, grassland, water body, built-up land, and unused land. The combined accuracy of the six classes was higher than 90% (Liu et al, 2010). Land use and land use change for the six classes and their subclasses (such as saline, swamp, and snow) in 1990, 2000 and 2010 were used in this study.…”
Section: Land Use Datamentioning
confidence: 99%
“…Therefore, accurately monitoring the regional expansion of built-up areas in China is essential (He et al 2006;Liu et al 2012 (Cao et al 2009;Liu et al 2012;Bhatti and Tripathia 2014), are commonly used. However, because of the limited geographic coverage of medium-and high-resolution images, these methods require a large number of scenes to cover the regional and national scales (Liu et al 2003(Liu et al , 2005(Liu et al , 2010Zhang, He, and Liu 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, accurately monitoring the regional expansion of built-up areas in China is essential (He et al 2006;Liu et al 2012 (Cao et al 2009;Liu et al 2012;Bhatti and Tripathia 2014), are commonly used. However, because of the limited geographic coverage of medium-and high-resolution images, these methods require a large number of scenes to cover the regional and national scales (Liu et al 2003(Liu et al , 2005(Liu et al , 2010Zhang, He, and Liu 2014).Nighttime stable light (NSL) images on board the Operational Line-scan System (OLS) of the Defense Meteorological Satellite Program (DMSP), which uses a low-light detecting sensor to detect city night lights (Elvidge et al 1997(Elvidge et al , 1999, were first demonstrated to be capable of mapping built-up urban areas by Croft (1978) and Kramer (1994). Subsequent studies demonstrated the superiority of DMSP-OLS NSL in extracting the built-up urban areas at global (Elvidge et al 1997(Elvidge et al , 1999(Elvidge et al , 2007 (Imhoff et al 1997a(Imhoff et al , 1997bSmall, Pozzi, and Elvidge 2005;Lu et al 2008;Cao et al 2009;Shi et al 2014;Wei et al 2014).…”
mentioning
confidence: 99%